2016
DOI: 10.21859/jrehab-1702136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Seat Cushions and Ball Chairs on Classroom Behavior of Students with Autism Spectrum Disorder

Abstract: Objective Children with Autism Spectrum Disorder (ASD) have a lot of sensory integration problems, which severly interfere with their learning process in the classroom; therefore, they confront with difficult problems in academic achievements. As a result, they need environmental modification to resolve sensory seeking behaviors and improve their educational success. Considering the effects of sensory stimulation and integration in children with ASD, this study aimed to examine the impacts of sitting on a ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Alternative seatings, such as therapy balls or air cushions, have been found to be effective for improving attention and in-seat behaviors in children with ASD in multiple single-case design studies (Bagatell et al., 2010; Krombach & Miltenberger, 2020; Matin Sadr et al., 2015; Schilling & Schwartz, 2004). For example, Schilling and Schwartz (2004) used a single-subject withdrawal design and found that the use of therapy balls increased engagement and in-seat behavior for four preschool-age children with ASD.…”
Section: Overview Of Evidence For Sensory-based Interventionsmentioning
confidence: 99%
“…Alternative seatings, such as therapy balls or air cushions, have been found to be effective for improving attention and in-seat behaviors in children with ASD in multiple single-case design studies (Bagatell et al., 2010; Krombach & Miltenberger, 2020; Matin Sadr et al., 2015; Schilling & Schwartz, 2004). For example, Schilling and Schwartz (2004) used a single-subject withdrawal design and found that the use of therapy balls increased engagement and in-seat behavior for four preschool-age children with ASD.…”
Section: Overview Of Evidence For Sensory-based Interventionsmentioning
confidence: 99%
“…Incorporating stability balls and a variety of kinesthetic equipment (i.e., standing desks, kneel‐and‐spin desks, under‐desk pedals, and bouncy bands) has also demonstrated increases in on‐task behavior of general education elementary students (Fedewa & Erwin, 2011; Flippin et al, 2020) whereas others have not (Olson et al, 2019). The results may be specific to the needs of the students, as stability ball use among some elementary students with autism spectrum disorder (ASD) has shown improvements in on‐task and in‐seat behavior (Matin Sadr et al, 2017). Additionally, elementary students with Attention Deficit Hyperactivity Disorder (ADHD) have benefitted from stability ball use as study results indicated increased attention and on‐task and in‐seat behavior (Fedewa & Erwin, 2011; Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%